2019
DOI: 10.32479/ijeep.8030
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Economic Growth: The Evidence From India

Abstract: The oil price shock of the 1970s and its disruptive impact on the economic activities all over the world dragged the attention of researchers to study the interaction between energy and real output. However, no conclusive evidence could be submitted about the direction of causality between the two. The present study has been an attempt to understand such relationship in the case of India. The paper has used the data from 1971 to 2014 and has found long run stable relationship between energy use and real output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
1
14
1
Order By: Relevance
“…Energy price and investment are the other important determinants of energy consumption and income, respectively. Furthermore, the results of research from Sultan and Alkhateeb (2019) revealed that in the short term there is a direct relationship between energy consumption and economic growth, and in the long run found a two-way relationship between energy and economic prosperity in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Energy price and investment are the other important determinants of energy consumption and income, respectively. Furthermore, the results of research from Sultan and Alkhateeb (2019) revealed that in the short term there is a direct relationship between energy consumption and economic growth, and in the long run found a two-way relationship between energy and economic prosperity in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study shows that the main burden of the [11,12,13]. Also there is a positive relation between energy consumption and carbon dioxide emissions [7]. Therefore, the development of manufacturing increases carbon dioxide emissions.…”
Section: Discussionmentioning
confidence: 73%
“…In order to enhance sustainability and development, it is necessary to reduce the carbon intensity of human well-being (CIWB). Technology spillovers can increase CIWB; while economic development has positive effect on CIWB, invasive technology and industry has negative effect on CIWB [7]. Therefore it is necessary to balance ecological and environmental concerns with human well-being and economic development, which is the pathway to sustainable development [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have also scrutinized the causal effects between energy consumption and economic growth (e.g. Ghosh, 2002;Bartleet and Gounder, 2010;Dagher and Yacoubian, 2012;Shahbaz and Feridun, 2012;Pao and Fu, 2013;Pao et al, 2014;Shahbaz et al, 2015;Alper and Oguz, 2016;Tang et al, 2016;Zakaria and Shamsuddin, 2016;Kahia et al, 2017;Rafindadi and Ozturk, 2017;Sultan and Alkhateeb, 2019), which can be categorized into four hypotheses, each of which has an essential implication for energy policy (Al-Mulali et al, 2013). These hypotheses are identified as growth, conservation, feedback and neutral hypotheses; where these hypotheses are essential to be studied to reach a relevant theoretical, empirical and policy implications (Odhiambo, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%